An Investigation of Interactivity Function of Discourse Markers used by Non-Native English Speakers in a Casual Conversation - Sujarwati, Iis (Universitas Islam Negeri Raden Intan Lampung, 2017)
This study reports on an investigation into the use of Discourse Markers in the matter of interactivity function during an individual task performance. The study involved four (4) Non-Native English Speaker students who are classmates of English class. The context of the conversation was in terms of casual conversation which happened before class. The participants discussed about ‘task’ and ‘holiday’. The conversation consisted of 318 turns in 14 minutes 38 seconds (14:38’). To reach the goal, the student’s expressions were recorded and transcribed based on turns. The transcription was then analyzed and interpreted. The findings show the DMs of interactivity mostly used in the conversation are “well, yeah” which are aimed to provide a fairly non-committal response to what has just been said.